Control design, simulation and validation of a turbo-machinery auxiliary plant. (August 2017) - Conti, Roberto; D'Adamio, Pierluca; Galardi, Emanuele; Meli, Enrico; Nocciolini, Daniele; Pugi, Luca; Rindi, Andrea; Lo Presti, Giulio; Rossin, Stefano
In the oil and gas industry, the testing of auxiliary lubrication plants represents an important preliminary activity before the whole turbo machinery train (including the auxiliary lubrication plant) can be put in operation. Therefore, the employment of both efficient and accurate plant models becomes mandatory to synthesize satisfactory control strategies both for testing and normal operation purposes. For this reason, this paper focuses on the development of innovative real-time models and control architectures to describe and regulate auxiliary lubrication plants. In particular, according to the Bond-Graph modelling strategy, a novel lumped parameter model of the lube oil unit has been developed to properly optimize the behaviour of this unit if it is controlled . The code has been compiled and uploaded on a commercial real-time platform, employed to control the pressure control valve of the physical plant, for which a new controller has been developed. The comparison between the data obtained from the simulated system and acquired from the physical plant shows good agreement and the good performance and reliability of the proposed model and control strategy. The modelling approach and the control strategy have been developed in collaboration with GE Nuovo Pignone S.p.a. while the experimental data were acquired in a plant located in Ptuj (Slovenia).